2013
DOI: 10.1037/a0032655
|View full text |Cite
|
Sign up to set email alerts
|

Is liability to recurrent major depressive disorder present before first episode onset in adolescence or acquired after the initial episode?

Abstract: Many individuals who experience a major depressive episode will subsequently develop recurrent episodes. Although numerous studies have investigated predictors of recurrent episodes, methodological limitations have made it difficult to determine the extent to which liability to recurrent major depressive disorder (rMDD) exists prior to first onset or develops after first onset. This study used a prospective design in a community sample of adolescents to examine variables before and after first onset MDD as pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 34 publications
3
30
0
Order By: Relevance
“…Our finding of increased rates of parental MDD for early-onset MDD is consistent with evidence from family and twin studies that early-onset depressive disorders are more heritable than later-onset depressive disorders (Bland et al, 1986; Klein et al, 2002; Klein et al, 2001; Klein et al, 2004; McGuffin et al, 1996; Pettit et al, 2013; Weissman et al, 1984). In contrast, our finding that MDD recurrence was not associated with increased rates of parental psychiatric disorders, after accounting for age of onset, suggests that previous evidence of greater heritability for recurrent MDD may be attributable to its typically earlier age of onset.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our finding of increased rates of parental MDD for early-onset MDD is consistent with evidence from family and twin studies that early-onset depressive disorders are more heritable than later-onset depressive disorders (Bland et al, 1986; Klein et al, 2002; Klein et al, 2001; Klein et al, 2004; McGuffin et al, 1996; Pettit et al, 2013; Weissman et al, 1984). In contrast, our finding that MDD recurrence was not associated with increased rates of parental psychiatric disorders, after accounting for age of onset, suggests that previous evidence of greater heritability for recurrent MDD may be attributable to its typically earlier age of onset.…”
Section: Discussionsupporting
confidence: 89%
“…We expected to find increased rates of parental MDD and other psychiatric disorders for offspring with early-onset and recurrent MDD, as suggested in earlier research (Bland et al, 1986; Klein et al, 2002; Klein et al, 2004; Pettit et al, 2013; Weissman et al, 1984). We further hypothesized that (a) premorbid negative emotionality would be highest for early-onset, recurrent MDD, as suggested by our findings in late adolescence and young adulthood (Wilson et al, 2014; Wilson et al, in press); (b) higher disconstraint would predict early-onset MDD, as suggested in our previous work (Wilson et al, 2014); and (c) lower premorbid positive emotionality would be specific to recurrent MDD.…”
Section: Studymentioning
confidence: 56%
See 1 more Smart Citation
“…Can we identify and ameliorate the factors associated with higher risk of recurrence and help those more vulnerable to recurrence to cope effectively with stressful life events? Although it is not possible at baseline to predict with a high degree of certainty which adolescents are most likely to have a recurrence, we know that gender, anxiety, a parental history of recurrent depression, and pre-MDE experiences of subthrehold depression are likely to be among the risk factors (Curry et al, 2011;Pettit, Hartley, Lewinsohn, Seeley, & Klein, 2013). These findings suggest that recurrence prevention programs could be tailored to address such specific risk factors.…”
Section: Preventing Recurrencementioning
confidence: 82%
“…Youth with depression may still face impairment even following remission or successful treatment (Garber & Horowitz, 2002; Rao et al, 1995), and depression earlier in life predicts impairment into adulthood (Birmaher et al, 2002; Dunn & Goodyer, 2006; Lewinsohn, Rohde, Seeley, Klein, & Gotlib, 2003). Although most children and adolescents with a major depressive episode recover naturally (Essau, 2007), relapse rates are high, with the majority of youth experiencing another episode within several years later (Birmaher et al, 2002; Kovacs, 1996; Pettit, Hartley, Lewinsohn, Seeley, & Klein, 2013). …”
mentioning
confidence: 99%